THE EFFECT OF HALAL CERTIFICATION ON BRAND LOYALTY BY MEDIATION OF PURCHASE INTENTION TOWARDS LOCAL INDONESIAN PRODUCTS : THE CASE OF GEN-Z INDONESIA MALAYSIA BORDER - Sinaga, Samuel; Astika, Sri; Nasrudin, Abdul Rohman (ITB AAS INDONESIA Surakarta, 2025)
Indonesia, as the country with the largest Muslim population in the world, places great importance on halal certification in its food industry. The halal certification issued by the Indonesian Ulema Council (MUI) serves as official proof that food products comply with Islamic law, and it has become a key requirement for producers operating in this sector. This study aims to analyze the influence of Halal Certification on Brand Loyalty, both directly and indirectly through Purchase Intention as a mediating variable. Focusing on domestic consumers in a predominantly Muslim market, the research employs path analysis to examine the relationships among these variables. The findings show that Halal Certification positively and significantly affects both Purchase Intention and Brand Loyalty, while Purchase Intention also has a positive and significant impact on Brand Loyalty, confirming its mediating role. These results suggest that halal-certified products enhance consumer trust, stimulate purchasing intentions, and build long-term loyalty toward the brand. Consequently, Halal Certification emerges as a strategic element for strengthening brand competitiveness and consumer confidence in Indonesia’s food industry.